Recent Advances in the Use of Drosophila melanogaster as a Model to Study Immunopathogenesis of Medically Important Filamentous Fungi. - Hamilos, G.; Samonis, G.; Kontoyiannis, D.P. (International journal of microbiology., 2012)
Airborne opportunistic fungi, including Aspergillus and other less common saprophytic molds, have recently emerged as important causes of mortality in immunocompromised individuals. Understanding the molecular mechanisms of host-fungal interplay in robust experimental pathosystems is becoming a research priority for development of novel therapeutics to combat these devastating infections. Over the past decade, invertebrate hosts with evolutionarily conserved innate immune signaling pathways and powerful genetics, such as Drosophila melanogaster, have been employed as a means to overcome logistic restrains associated with the use mammalian models of fungal infections. Recent studies in Drosophila models of filamentous fungi demonstrated that several genes implicated in fungal virulence in mammals also play a similarly important pathogenic role in fruit flies, and important host-related aspects in fungal pathogenesis are evolutionarily conserved. In view of recent advances in Drosophila genetics, fruit flies will become an invaluable surrogate model to study immunopathogenesis of fungal diseases.